The Effect of Profitability, Liquidity, and Company Size on Tax Planning With Transparency As A Moderation Variable in Food and Beverage Companies Listed on The IDX in 2018-2022 - I Putu Arka Pradipta; Abdul Hadi Achmad; Kumba Digdowiseiso (Jurnal Syntax Transformation, 2024)
This study aims to analyze and determine the effect of Profitability, Liquidity, Company Size on Tax Planning with Transparency as a moderating variable in Food And Beverage Companies listed on the Indonesia Stock Exchange in 2018- 2022. The data source in this study uses secondary data, namely the annual financial statements of Food And Beverage companies in 2018-2022. The research population was 30 Food And Beverage companies for 2018-2022. This study uses the Purpose Sampling method and there are 20 company samples processed using IBM SPSS Statistics 26. The results of this study indicate that Profitability, Liquidity, and Company Size have a significant negative effect on Tax Planning. Transparency is not able to moderate the effect of Profitability, Liquidity, Company Size on Tax Planning, but the presence of Transparency as a moderating variable can approach the standard test value on the effect of Profitability, Liquidity, and Company Size on Tax Planning.